Report of the 9th Annual All Ohio Junior High Guidance Conference. Up, Up With People Through a Galaxy of Services for the Individual. - Ohio School Counselors Association; Ohio School Counselors Association ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Approximately 300 school counselors, other educators, and guests from the state of Ohio met to discuss and evaluate the many services offered to school-age children by the helping professions. Eighteen workshop sessions are summarized in this report. These workshop sessions were concerned with the following: (1) sex education and the health curriculum; (2) social work services in the inner city; (3) the role of the instructional resource center; (4) help for the learning disabled child; (5) career orientation; (6) "sheltered training experience project" (a program for the physically handicapped in Toledo); (7) family life education; (8) a drug intervention center; (9) student rights-student unrest; (10) behavior modification; (11) teaching the unteachables; (12) adapting materials to the educable mentally retarded; (13) the problems of planning group testing programs; (14) negotiating counselors' salaries; (15) the concept and process of staff development; (16) the Hillcrest project -- on on-the-job training program; (17) regional pupil personnel centers; (18) ASCA issues related to middle and junior high schools. The related theme of accountability was dealt with in each of the 18 workshops. (RK)
Sponsoring Agency: Ohio State Dept. of Education, Columbus. Div. of Guidance and Testing.
ERIC Note: Reprint from proceedings of 9th Annual All Ohio Junior High Guidance Conference, May 7, 1971, Toledo, Ohio.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Counseling; Counselor Evaluation; Counselor Role; Guidance; Guidance Objectives; Guidance Programs; Pupil Personnel Services; Social Work; Workshops